Investigating the Correlation Between Computer Tests (CANTAB) and Functional Cognitive Tests (LOTCA) With the Participation of People With Multiple Sclerosis in Daily Life Activities. - Faraji, Milad; Haghgoo, Hojjat Allah; Peshyareh, Ebrahim; Monfared, Elyas; Vahedi, Mohsen (Archives of Rehabilitation, 2023)
Objective Multiple sclerosis (MS) is a disorder that involves the central nervous system. Cognitive impairments in patients with MS have a direct and significant impact on their performance in the activities of daily living, and hence their social participation is disrupted. Thus, exploring cognitive domains can help us make clinical decisions and interventions. To cognitively rehabilitate these people and estimate the relationship between cognitive performance (computer test and performance test) and the level of participation, we should examine the correlation between these two domains. This study aims to determine the correlation between social participation and two types of cognitive assessments: computerized and functional. Materials & Methods The present study was a cross-sectional study, and sampling was done by available sampling. The target population was patients with MS admitted to the MS center of Isfahan City, Iran, provided that they met the inclusion criteria in the winter of 2021. Forty-five patients with MS (9 males and 36 females) with an expanded disability status scale between 1 and 5 were selected by available sampling. To assess their cognitive performance, Cambridge neuropsychological test automated battery (CANTAB) and the Lowenstein occupational therapy cognitive assessment (LOCTA) functional test were used. Also, the community integration questionnaire (CIQ) was used to determine the level of participation. The data were then processed with SPSS. Results Based on the study results on the intensity and relationship between the measures, there is integration in targeted activities with all measures of LOTCA and CANTAB. This measure had a significant relationship with orientation, visual perception, and motor praxis from the LOTCA test and Delayed matching to sample test (DMS) from the CANTAB test. Notable results include a high correlation between home integration of the CIQ and the stocking of Cambridge test from CANTAB (r=0.353), and social integration of the CIQ with the DMS from CANTAB (r=0.538), integration in purposeful and productive activities of the CIQ with the motor proxy from LOTCA (r=0.422). Conclusion According to the results, both tests have a high correlation with the CIQ. So, computer test, which has a good correlation with participation, can be used alongside the performance test.